Perception of Visitor on Parking Lot with Charge - Nur Ellyana Farhana Muhd Jasmin Shahizan; Siti Nursyafiqah Shikh Hasmat (ALTSA Publisher, 2023)
This research is to investigate the perception of visitors of the parking lot with a charge at Pantai Sepat. This research will investigate the number of vehicles at Pantai Sepat and identify the percentage of visitors. The target respondents for this research are teenagers, tourists and local people around there. Furthermore, the questionnaires were distributed online by using a simple random sampling technique. As a result, 50 sets of questionnaires were collected to see whether it's reasonable for us to charge for parking at Pantai Sepat. Meanwhile, the independent variable for convenience shows that there is a positive relationship with the dependent variable. Moreover, this research shows a clearer overview of whether it is reasonable for us to make a charge on the parking lot at Pantai Sepat. Lastly, the limitation of doing this research was identified, and implications for further research were recommended.